Fostering Student Happiness in Learning During the Covid-19 Pandemic: A Phenomenological Study in Elementary School - Wrediningsih, Wresti; Sanjaya, Ade Wira (RSF Conference Series: Business, Management and Social Sciences, 2024)
Students` comfort while at school plays a vital role in learning. Teachers` representation is required to foster students` well-being. This mini research explores the perspective of the 1st-grade elementary school teachers on student well-being and their experience in promoting it. The data was obtained through an interview with one teacher and analyzed using the interpretative phenomenological analysis (IPA) approach. The analysis results showed four themes: the principles of student well-being, the ways the teacher encourages students` well-being, and support and challenges for the teacher. This study concludes that the role of teachers is very important in providing a pleasant learning atmosphere for students. There are many ways that teachers can be creative with support from schools and the community